Songs of Christmas - Spencer, Katherine, 1955- (Kinkade, Thomas, 1958-2012. Cape Light novel., 2013)
"It's the happiest time of year, but the Christmas spirit is lost on Lillian Warwick. Her beloved Ezra's failing health requires the help of an aide. Estrella Hernandez quickly wins Ezra's admiration, but drives Lillian absolutely crazy. When a brutal storm forces Estrella's family to take shelter under Lillian's roof, her humbuggery is pushed to its limits. Amanda Harding comes home to Cape Light, feeling at loose ends in her life. A recent graduate and accomplished musician, she hopes to find a seat in a big-city symphony. In the meantime, the job of music director at Reverend Ben's church seems good enough. Unfortunately, she must share her practice space with Gabriel Bailey, who is restoring the stained glass windows. The rough-around-the-edges craftsman is Amanda's opposite in every way. Still, something rare and wonderful flourishes between them. When Amanda is offered an ideal opportunity to perform her music far from Cape Light, Gabriel encourages her to pursue it. But must she choose between her music and losing Gabriel forever? As Christmas nears, Lillian and Amanda both hearken to the sound of their favorite carols, but soon learn that sometimes the sweetest songs of Christmas are still waiting to be sung."--